PENGUATAN PERILAKU KESELAMATAN - Fuadi, Yan; Ramdan, Muhamad; Sunyanti, Sunyanti; Ananta, Erwin; Hardyono, Hardyono; Zainal, Muhammad Isradi (Program Studi D4 K3 Universitas Balikpapan, 2022)
The basis of human behavior is: How a person conducts himself (acts). Individual attitude. Observable actions of a person. From several major incidents that have occurred in the world such as the incidents at Flixboro, Kegworth and Moorgate and Piper Alpha, there is evidence that there have been failures and discrepancies where human behavior is a significant causative factor. Dialogue and discussion with workers during OSH observations is a way to reveal the antecedents & consequences behind the behavior shown by workers, so that the right strategy can be taken to change at-risk behavior and strengthen safe behavior.